PEMANFAATAN PANAS MATAHARI PADA DINDING LUAR BANGUNAN SEBAGAI SUMBER ENERGI LISTRIK MENGGUNAKAN GENERATOR TERMOELEKTRIK - Kuncoro, Wahyu; Rifky, Rifky; Mugisidi2, Dan; Muharom4, Vazri (Fakultas Teknik Universitas Wahid Hasyim, 2021)
This research utilizes solar thermal energy that absorbed by the outer wall of the building which facing north. The heat energy is converted into electrical energy using a thermoelectric generator type TEC 12706. To maintain the cold side area of TEC 12706 heatsinks are circulated with circulating water cooling fluid with a discharge of 1.8 lpm and the temperature is not more than 3oC. The study was conducted with a simulation tool composed of several materials such as glass, aluminum, styrofoam and heatsink. The test is conducted from 06.00 WIB until 18.00 WIB for 3 days. The parameters measured are light intensity, wind speed, water flow, temperature, electric voltage and electric current contained in the test equipment. The research results get a maximum output power of 0.0024 W, thermoelectric efficiency and system efficiency.